Editorial Comments - Marie Poggenpoel; Annatjie Botes (AOSIS, 2001)
All the articles in this edition address the issue of challenges in a person's ability to actualise his/her own full potential in a quest for health. Opsomming Al die artikels in hierdie uitgawe spreek die aspek van uitdagings aan in 'n persoon se vermoë om sy/haar eie volle potensiaal te aktualiseer in 'n strewe na gesondheid. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.